Ghosts, toast, and other hazards - Tan, Susan (Roaring Brook Press, 2023)
When her stepfather leaves and her family loses their home to fire, twelve-year-old Chinese-American Monica, or Mo, struggles with anxiety, but the chance to hunt an elephant ghost -- and the promise of a new friend -- help convince her to live a little more dangerously.